Improving health and safety and injury management performance in large organisations: preliminary insights from an evaluation of the Victorian employer performance management program. (1st March 2011) - Mitsopoulos-Rubens, E; Lenn, M; Trotter, M; Day, L
Abstract : Introduction: The Employer Performance Management Program (EPMP) is an initiative of the workplace safety authority in Victoria, Australia (WorkSafe Victoria). It aims to achieve (1) greater insight into factors affecting occupational health safety (HS) and injury management (IM) in large organisations and (2) consequent HS and IM performance improvement. The EPMP includes a HS and IM performance audit, performance report preparation and action plan development. We report preliminary findings from a comprehensive evaluation of the EPMP. Methods: Focus groups were held with WorkSafe EPMP performance managers after the first round of organisations had received their performance reports, and again 6 months later after the second round of organisations had received their reports. A semi-structured discussion guide was used to identify any potential barriers to the programs delivery and effectiveness. Results: Themes to emerge included an overall positive perception of the EPMP in terms of its strategic focus and proactive, collaborative approach. Concerns were raised regarding the adequacy of the audit tool, for example, in terms of its suitability to multi-site/division organisations and insufficient coverage of HS issues relative to IM. Low organisational engagement was identified as a potential barrier to the programs success. Conclusion: The EPMP has the capability to produce sustainable change in the HS and IM practices and performance of large organisations. The potential barrier of low organisational engagement needs to be addressed to optimise program success. These results will be incorporated into the broader evaluation, which includes a claims analysis and a cohort study of EPMP organisations.